The Effects of Reinsurance in Financing Children's Health Care - David E.M. Sappington; Sema K. Aydede; Andrew Dick; Bruce Vogel; Elizabeth Shenkman (SAGE Publishing, 2006)
This paper examines the effects of reinsurance on the financial performance of health plans serving enrollees in a State Children's Health Insurance Program (SCHIP). We demonstrate that simple reinsurance policies can reduce substantially the variation in the financial performance of plans with different case mixes, even when the plans bear the cost of the reinsurance and are not fully insured against large expenditures on individual enrollees.